Molecular virology of hepatitis B virus, sub‐genotype C4 in northern Australian Indigenous populations. Issue 4 (13th January 2014) - Littlejohn, M.; Davies, J.; Yuen, L.; Edwards, R.; Sozzi, T.; Jackson, K.; Cowie, B.; Tong, S.; Davis, J.; Locarnini, S.
<x xml:space="preserve">Abstract</x> Indigenous Australians experience a significant health burden from chronic hepatitis B infection; however, the strain of hepatitis B virus (HBV) found among Indigenous Australians has not been well characterized. Blood samples were collected from 65 Indigenous Australians with chronic HBV infection from across the Top End of Australia's Northern Territory. Phylogenetic analysis of HBV from these samples revealed that 100% of the isolates were genotype C, sub‐genotype C4, expressing the serotype ayw3. This strain is a divergent group within the HBV/C genotype, and has only been described in Indigenous Australians. Evidence of recombination was suggested by discordant phylogenetic clustering of the C4 sequences when comparing the full genome to the surface region and confirmed by recombination analysis which showed the surface gene region to be most closely related to genotype J, while the remaining regions of the genome were most similar to genotype C sequences. Mutational analysis revealed the presence of multiple mutations that have been linked with more rapid liver disease progression and an increased risk of hepatocellular carcinoma. These mutations were detected in the majority of sequences examined. Variants associated with vaccine failure were detected as the predominant viral quasi‐species in 3/35 samples. In summary, the HBV C4 variant found in this population has a high potential to cause advanced liver disease and to escape vaccination programs. Further in vitro functional and natural history studies are warranted in order to determine the clinical and public health consequences of infection with the HBV C4 variant in these communities. J. Med. Virol. 86:695–706, 2014. © 2014 Wiley Periodicals, Inc.